Signal Transduction Therapy in Pancreatic Cancer - Sun, Xiaotian; Li, Zhaoshen; Li, Min (Current Signal Transduction Therapy, 2014)
Signal transduction has been acknowledged to be involved in various cell biological processes. And it is proved that multiple signaling pathways have been associated with the development and progression of pancreatic cancer, which remains one of the most devastating human diseases. Newly developed drugs targeting these aberrant signaling pathways show bright prospect in improving the therapeutic efficacy and outcome for patients with pancreatic cancer. Here we overview the pancreatic cancer related signaling pathway disorders and the corresponding promising targeted therapeutic regimens.
Keywords: Pancreatic cancer